Reliability of a cycle ergometer peak power test in running-based team sport athletes: a technical report - Wehbe, G. M.; Gabbett, T. J.; Hartwig, T. B.; Mclellan, C. P. (The Journal of Strength and Conditioning Research, 2015)
Given the importance of ensuring athletes train and compete in a nonfatigued state, reliable tests are required to regularly monitor fatigue. The purpose of this study was to investigate the reliability of a cycle ergometer to measure peak power during short maximal sprint cycle efforts in running-based team sport athletes. Fourteen professional male Australian rules footballers performed a sprint cycle protocol during 3 separate trials, with each trial separated by 7 days. The protocol consisted of a standardized warm-up, a maximal 6-second sprint cycle effort, a 1-minute active recovery, and a second maximal 6-second sprint cycle effort. Peak power was recorded as the highest power output of the 2 sprint cycle efforts. Absolute peak power (mean ± SD) was 1502 ± 202, 1498 ± 191, and 1495 ± 210 W for trials 1, 2, and 3, respectively. The mean coefficient of variation, intraclass correlation coefficient, and SE of measurement for peak power between trials was 3.0% (90% confidence intervals [CIs] = 2.5-3.8%), 0.96 (90% CIs = 0.91-0.98), and 39 W, respectively. The smallest worthwhile change for relative peak power was 6.0%, which equated to 1.03 W·kg-1. The cycle ergometer sprint test protocol described in this study is highly reliable in elite Australian rules footballers and can be used to track meaningful changes in performance over time, making it a potentially useful fatigue-monitoring tool.